2021
DOI: 10.3233/hsm-201012
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring training programs for sustainability management based on the training needs assessment

Abstract: BACKGROUND: Human resource development in sustainability is a prerequisite of enhancing the success of any organization. Education for sustainable development has been recognized as a key process to support employees’ skills development to positively reoriented their behavior to the sustainable development values and principles. In the article context, based on a synthetic literature review for charting the sustainability taxonomy, there has been created a first general inventory of topics needed to be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…As Zeleny [32] states, intercultural experience is needed for acquiring the understanding and knowledge of Integrated Productive Environment (IPE) as an essential prerequisite where cultural adjustments to build environments is required [32]. Therefore we could say that for interculturally competent individuals, some similar approach as "theoretical knowledge + examples of good practices + exercises + individual projects" [33] is vital too. This means that interculturally competent individuals (so be it students or teachers) cannot become only with heaving theoretical knowledge about different cultures.…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…As Zeleny [32] states, intercultural experience is needed for acquiring the understanding and knowledge of Integrated Productive Environment (IPE) as an essential prerequisite where cultural adjustments to build environments is required [32]. Therefore we could say that for interculturally competent individuals, some similar approach as "theoretical knowledge + examples of good practices + exercises + individual projects" [33] is vital too. This means that interculturally competent individuals (so be it students or teachers) cannot become only with heaving theoretical knowledge about different cultures.…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…It showed that those who received information emphasizing the system's functionality had higher expectations of the system's functionality and crashworthiness in a variety of driving scenarios, as well as a gap in crash expectations pre-driving but not post-driving after different training modes. Literature [13] points out that sustainable human resource development is the basis for organizational success, and research on how to set up a training program based on the case of "management positions" to study the variables results show that the best training program is a combination of theoretical knowledge, examples of practice, repeated practice and individual projects to try their hands. Literature [14] analyzed the status quo and problems of e-commerce talent training in China and explored the cooperation mode and cooperation mechanism of school-enterprise cooperation to incubate e-commerce talents together, which provides a reference for e-commerce talent training and theory.…”
Section: Introductionmentioning
confidence: 99%
“…Xiaoxu Chen, Hanyang Chen and Jinhua Xu. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] …”
mentioning
confidence: 99%
“…A survey based on a designed questionnaire for the assessment of training needs in the field of leadership for sustainable development [18]. The research aim was to characterize the SD skills and competencies of managers and specialists included in the sample, which consisted of 207 respondents who were employees of different companies (from Austria, France, Romania, and Slovenia), with a balanced structure of management position and distribution of age.…”
mentioning
confidence: 99%
“…The two exhaustive studies carried out [17,18] contributed to the creation of a critical mass of knowledge regarding the understanding of the needs of companies and their managers regarding SD management. Two fundamental ideas (needs and requirements) constitute the premise of further research for the development of an approach for the monitoring and control of the sustainable development strategy.…”
mentioning
confidence: 99%